Ayurveda Management of Garbhini Vibandha w.s.r. to Constipation in Pregnancy- A Conceptual Study - Rohit Tiwari; Sucheta Ray; Varsha Jadhao; Priyanka Hajare; Ekta Singh Parihar (AYUSHDHARA, 2024)
Constipation is among minor ailment during pregnancy. There are anatomical, physiological and hormonal adaptations during pregnancy phase, due to these changes every pregnant woman faces some difficulties like heartburn, nausea, vomiting, pedal oedema, constipation in all three trimesters. Garbhini Vibandha or constipation during pregnancy, characterized by difficulty in bowel movements. Some gynaecological diseases, stress, hormonal imbalance leads to irregular bowel habits in women. Most of the pregnant women has this complains. Acharya Kashyapa mentioned that the diseases which are seen in any other individual will see in pregnant females also as Dosha, Dushya of the body are same. According to Ayurvedic principles, and this condition primarily results from an imbalance in Vata dosha, mainly Apana Vata, which governs the elimination process. The condition may be exacerbated by the natural physiological and hormonal changes during pregnancy, dietary factors, reduced physical activity, and psychological stress. Ayurveda emphasizes a holistic approach in managing Garbhini Vibandha, focusing on dietary modifications, lifestyle changes, and the use of specific herbs to balance the Dosha. Herbal remedies such as Triphala kwatha, Haritaki, Gur, Nagara, are commonly used to alleviate constipation. In this article, we want to focus on mode of action of these drugs on Garbhini and the main precautionary point is that these medications should be taken under supervision of doctor. Over dose intake or wrongly intake can cause other health problems.